The Democratic Republic of Congo – elections 2016. Road to democracy? - Kumar, Keerthi Sampath (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
It is a crucial time in African politics, as many nations in the continent will be holding elections over the next twelve months. The Democratic Republic of Congo (DRC) is also scheduled to hold a presidential election in 2016. However, the question that has left the nation in a political turmoil is whether the current President, Joseph Kabila will pave the way for a smooth democratic transition or, if he refuses to step down, will the country deteriorate into further chaos and instability? This paper looks at the current political situation in the DRC and assesses the challenges that lie on its road to democracy. In the following sections, it also analyses the role of the various actors in the current crisis including the opposition, civil society and the international community. The last section of the paper considers and lays out some possible scenarios, as the country gets ready to hold its presidential elections in November 2016.

Afrykańska polityka znajduje się obecnie w punkcie zwrotnym, stojąc u progu wyborów, jakie w ciągu następnych dwunastu miesięcy zostaną przeprowadzone w wielu krajach tego kontynentu. Również w Demokratycznej Republice Konga (DRK) zaplanowano wybory prezydenckie w 2016 roku. Kraj popadł jednak w polityczny zamęt wobec pytania czy obecny prezydent, Joseph Kabila utoruje drogę pokojowej zmianie demokratycznej, czy też kraj stoczy się w pogłębiający się chaos i destabilizację, jeśli odmówi ustąpienia z urzędu. Artykuł przedstawia aktualną sytuację polityczną w DRK i ocenia wyzwania, wobec jakich kraj stoi na drodze do demokracji. Jego dalsza część poświęcona jest analizie ról, jakie w obecnym kryzysie odgrywają rozmaici aktorzy, tacy jak opozycja, społeczeństwo obywatelskie i społeczność międzynarodowa. Ostatnia część artykułu omawia możliwe scenariusze wydarzeń w czasie przygotowań kraju do wyborów prezydenckich w listopadzie 2016 roku.
Demokratyczna Republika Konga – wybory 2016. Droga do demokracji?
Keywords: Democratic Republic of Congo; democracy; elections 2016; Joseph Kabila; political turmoil; Demokratyczna Republika Konga; demokracja; wybory 2016; Joseph Kabila; zamęt polityczny